The Transformation of Islamic Boarding Schools (Pesantren) Education: A Bibliometric Overview - Fahim Abu Romadlan; Benny Prasetiya; Febry Suprapto; Khoiriyah (PT. Caesarindo Triloka Persada, 2026)
The transformation of pesantren education is a critical issue, given its strategic role in Indonesia's national education ecosystem. Pesantren, as one of the oldest educational institutions, faces the challenges of globalization and digitalization, necessitating changes in educational systems and governance. This study aims to analyze publication trends, identify influential authors, and map thematic developments in the field of pesantren education transformation using bibliometric analysis. The methodology used is bibliometric analysis, examining publication data from the Scopus database between 2019 and 2024, including annual trends, disciplinary involvement, and international collaborations. The findings indicate a significant surge in publications related to pesantren since 2019, with a primary focus on curriculum transformation, transformative leadership, and digital literacy. Influential authors such as Baharun, Hefner, and Lopes Cardozo highlight global collaboration in this research field. The novelty of this study lies in thematic mapping that illustrates the relationships between themes like adolescent agency, cultural change, gender, and digital transformation in pesantren education. The contribution of this research is to provide new insights for the development of pesantren education in line with global trends and Indonesia's national research priorities, supporting quality education through SDG 4.